2019
DOI: 10.1111/jerd.12462
|View full text |Cite
|
Sign up to set email alerts
|

Fracture analysis of monolithic CAD‐CAM crowns

Abstract: Purpose The aim of this study was to compare the integrity of zirconia, lithium disilicate, and zirconia‐reinforced lithium silicate CAD‐CAM crowns after being subjected to cyclic loading and then subjected to static loading until fracture. Material and Methods Zirconia (Zirkonzahn), lithium disilicate (LDS, Ivoclar Vivadent AG), and zirconia‐reinforced lithium silicate glass ceramic (ZLS) (Vita Suprinity, Vita Zahnfabrik) monolithic crowns were milled (n = 6). The crowns were bonded using composite resin ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
(116 reference statements)
0
21
0
Order By: Relevance
“…According to Kashkari et al [32], a sample size of 10 specimens per group was calculated to have a minimum difference between the two groups in terms of fracture toughness. The value of α was determined at 0.05 while the power of the test was 0.80.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kashkari et al [32], a sample size of 10 specimens per group was calculated to have a minimum difference between the two groups in terms of fracture toughness. The value of α was determined at 0.05 while the power of the test was 0.80.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in the same study, 18 samples were used in three different groups. Thus, the sample size of 20 is sufficient to have a statistically significant difference in cases between the two groups analysed [32].…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have clearly demonstrated that mechanical properties of zirconia, expressed by parameters like load-to-fracture values, are higher than those of LS 2 , which, from their part, are higher than those of ZLS; the number of fatigue loading cycles does not seem to affect the load-to-fracture of zirconia restorations [23].…”
Section: Low Temperature Degradation (Ltd) and Agingmentioning
confidence: 98%
“…Monolithic LS 2 , as well as Zirconia reinforced-Lithium Silicate ceramics (ZLS), offers higher fracture resistance than bilayered, hand-veneered zirconia [20], while a recent in vitro research has shown that load-to-fracture values of monolithic zirconia are higher than those of LS 2 ; the latter, in turn, are higher than those of ZLS [23].…”
Section: Lithium Disilicate Physico-chemical Features Optical and Mementioning
confidence: 99%
“…In recent years, a new CAD/ CAM ceramic material was manufactured to combine the esthetic properties of lithium disilicate and the mechanical properties of zirconia (8). Zirconia-reinforced lithium silicate glass-ceramic is composed of 10% of zirconia in terms of its weight, and these zirconia particles are dissolved inside the metasilicate glassy matrix (9)(10)(11). According to the manufacturer, the homogeneous distribution of zirconia particles improves material strength and finishing (12).…”
mentioning
confidence: 99%